Mapping Sarawak to the World International Art Exchange and Exhibition: Jakarta, Indonesia / Clement Jimel ... [et al.] - Jimel, Clement (Perpustakaan Tun Abdul Razak, 2024)
Welcome to "Mapping Sarawak to the World: International Art Exchange and Exhibition." This event is a celebration of the rich cultural heritage of Sarawak, as interpreted by its talented artists, and shared with the vibrant city of Jakarta. The essence of Sarawak’s unique heritage is encapsulated in each painting, offering a visual narrative through the region’s diverse traditions, natural beauty, and storied history. The concept of this exhibition revolves around the idea of cultural exchange. By bringing the essence of Sarawak's culture to an international audience, the exhibition aims to foster a deeper understanding and appreciation of the unique artistic expressions that arise from this Malaysian state. Sarawak’s artists draw inspirations from their lush landscapes, intricate colourful strokes, and the harmonious coexistence of its various ethnic groups. Their works not only depict the physical beauty of Sarawak but also delve into the spiritual and cultural narratives that define their identity. As we navigate through the exhibited works, we experience how art transcends geographical boundaries and cultural differences. The exchange facilitated by this exhibition bridges the cultural gap between Malaysia and Indonesia, emphasising our shared humanity and the universal language of art. Through this visual conversation, we hope to inspire a lasting connection and a deeper understanding between the people of Sarawak and Jakarta, celebrating diversity while finding common ground in our creative expressions.